Role of Sangguniang Kabataan chairpersons in Iloilo City its effects on personal development - Baello, Jo-An D.; Barte, Janice O.; Dolar, Nera S.; Lavilla, Vipa Marie L.
Executive Summary - There are several factors, which contributes to the personal development of the youth. Some of these are : their parents' upbringing, education, outside environment, and experiences. Youth organizations and sectors are established to enhance and improve their abilities and learning. The Sangguniang Kabataan is one of these youth groups, which aims to empower to youth, and give them the opportunity to lead and be lead. These youth leaders are given the direct and indirect responsibility over their subordinates and provide the due compensation and benefits that a government official deserves to receive. This study was conducted to determine the effects of the role in the Sangguniang Kabataan in the personal development of the SK Chairpersons. The group tried to identify if the powers and responsibilities, as well as the benefits and privileges availed from the Sangguniang Kabataan contributed to the overall development of these youth leaders. The methods used by the group in data gathering are questionnaires and personal interviews. The respondents for the questionnaires are SK Chairpersons, and interviews were conducted with the Assistant Director of the Department of Interior and Local Government and the SK Federation President of Iloilo City. The group found from the analysis made that. The Sangguniang Kabataan greatly contributed to the personal development of its leaders. These leaders improved politically, socially, morally and intelectually.